2010
DOI: 10.2190/om.60.4.b
|View full text |Cite
|
Sign up to set email alerts
|

Internet Method in Bereavement Research: Comparison of Online and Offline Surveys

Abstract: This study examines the reliability and validity of Internet research in bereavement. Recent literature demonstrates an increased interest in utilizing a more convenient, inexpensive, and rapid Internet method to collect data and recruit bereaved participants. For researchers, the Internet offers the possibility to learn more about grief from the growing online community of bereaved people. To explore the possible use of Internet tools in bereavement research, this study compares online survey method with trad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…In addition, we recruited our participants from grief support groups and websites related to grief and loss; being a member of grief support group may have impacted the perceived social support of the participants as well as their processes of meaning-making. Further, as previously mentioned, internet samples may have different characteristics than traditional samples (see Tolstikova & Chartier, 2010) and thus, the results of this study may not be generalized to all bereaved people.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In addition, we recruited our participants from grief support groups and websites related to grief and loss; being a member of grief support group may have impacted the perceived social support of the participants as well as their processes of meaning-making. Further, as previously mentioned, internet samples may have different characteristics than traditional samples (see Tolstikova & Chartier, 2010) and thus, the results of this study may not be generalized to all bereaved people.…”
Section: Discussionmentioning
confidence: 90%
“…Like all other data collection methods, internet-based data collection has strengths and limitations (see Kraut et al, 2004, for a discussion). For example, Tolstikova and Chartier (2010) reported that there is more variation in internet samples in terms of time since loss, cause of death, and relationship to deceased as compared to traditional samples. Despite their limitations, it has been reported in the literature that internet-based studies are valid (Kraut et al, 2004) and that the internet-based data are reliable and psychometrically equivalent to other forms of data collection (e.g., Meyerson & Tryon, 2003).…”
Section: Methodsmentioning
confidence: 99%
“…So far, there is lack of a sound body of evidence to establish whether there is any difference between bereaved persons who use memorial websites and those who do not. There is some indication that differences may not be substantial: One study compared an online survey with a traditional paper and pencil method, finding no difference in the degree of grief or according to most demographic variables, except that the online survey recruited more a demographically diverse sample (Tolstikova, –2010). Our sample also reflected substantial diversity of participants' background; we have no reason to assume that there was any systematic bias in recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in a study comparing online and offline survey research in general bereavement, the authors found online research to be valid and reliable [13]. The authors cite a number of benefits of online survey research, including convenience, reduced costs, increased access to a larger population, and increased access to a diverse range of people experiencing bereavement [13]. Online survey research also offers anonymity [13], which may encourage participation from stigmatised groups, including people exposed to suicide attempts and deaths.…”
Section: Introductionmentioning
confidence: 98%
“…Online surveys are likely to attract people who have an interest in this topic, yet present new challenges beyond those often reported in relation to other suicide research methodologies, which have resulted in delays to research projects or major changes to methodology to obtain ethical approval [11,12]. Nevertheless, in a study comparing online and offline survey research in general bereavement, the authors found online research to be valid and reliable [13]. The authors cite a number of benefits of online survey research, including convenience, reduced costs, increased access to a larger population, and increased access to a diverse range of people experiencing bereavement [13].…”
Section: Introductionmentioning
confidence: 99%